Lysinebacillum Bacteriemia in an Adult Cancer patient - Samuel Martinez-Vernaza (Asociación Colombiana de Infectología, 2022)
Lysinibacillus is a genus of rod-shaped gram-positive bacteria most often found in soil and plantlife, however, it has been isolated from air and from the human intestinal microbiome as well. The genus Lysinibacillus is most often disregarded when isolated in the laboratory; nevertheless, it usually acts as an opportunist in immunocompromise hosts with various mortality rates. Here we present a case of bacteriemia due to Lysinibacillus in a patient whose clinical history and risk factors suggested otherwise. It is crucial to pay attention to the identification of this types of organisms, particularly, when they come from techniques such as spectroscopy. This in order to have a broader picture when addressing this type of patients.